2010
DOI: 10.1093/intimm/dxq430
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cells of non-hematopoietic and hematopoietic origins express activation-induced C-type lectin, the ligand for killer cell lectin-like receptor F1

Abstract: Killer cell lectin-like receptor F1 (KLRF1) is an activating C-type lectin-like receptor expressed on human NK cells and subsets of T cells. In this study, we show that activation-induced C-type lectin (AICL) is a unique KLRF1 ligand expressed on tumor cell lines of hematopoietic and non-hematopoietic origins. We screened a panel of human tumor cell lines using the KLRF1 reporter cells and found that several tumor lines expressed KLRF1 ligands. We characterized a putative KLRF1 ligand expressed on the U937 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
0
24
1
Order By: Relevance
“…LLT1 is expressed by the NK cell line YT and several B cell lines, but no expression by nonhematopoietic cell lines has been reported. 25,26,34 Similarly, we found human NK cell lines and some other hematopoietic cell lines to express AICL, but in contrast to a previous report, 23 no AICL expression by the epithelial cell line HeLa or other nonhematopoietic cell lines. However, reports on expression of LLT1 and AICL by glioblastoma and liver cancer, respectively, indicate that tumor cells may aberrantly express these CLEC2 proteins.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…LLT1 is expressed by the NK cell line YT and several B cell lines, but no expression by nonhematopoietic cell lines has been reported. 25,26,34 Similarly, we found human NK cell lines and some other hematopoietic cell lines to express AICL, but in contrast to a previous report, 23 no AICL expression by the epithelial cell line HeLa or other nonhematopoietic cell lines. However, reports on expression of LLT1 and AICL by glioblastoma and liver cancer, respectively, indicate that tumor cells may aberrantly express these CLEC2 proteins.…”
Section: Discussioncontrasting
confidence: 76%
“…However, reports on expression of LLT1 and AICL by glioblastoma and liver cancer, respectively, indicate that tumor cells may aberrantly express these CLEC2 proteins. 23,35 We find that NK cell activation by monokines results in an upregulation of AICL and downregulation of NKp80 at the cell surface that is paralleled by changes in levels of the corresponding transcripts. Because changes in NKp80 transcript levels were moderate, additional regulatory mechanisms may contribute to the observed changes in cell surface expression.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…AICL is expressed preferentially on the surface of myeloid cells, especially on malignant leukemia cells, but not on nonmyeloid hematopoietic cells or nonhematopoietic cells (8). AICL expression increases the susceptibility of myeloid cells to NK cell-mediated cytolysis (7).…”
Section: Discussionmentioning
confidence: 99%
“…The only known ligand for NKp80 to date is expressed by hematopoietic cells, especially by malignant myeloid cells in acute myeloid leukemia and chronic myeloid leukemia, and by non-hematopoietic cells, including carcinoma and melanoma cells (8). Researchers have already demonstrated that expression of AICL, which engages NKp80, increases the susceptibility of myeloid cells to NK cell-mediated cytolysis.…”
Section: The Capacity Of Natural Killer (Nk) Cells To Mediate Fc Recementioning
confidence: 99%